COVID-19, Tourism, and Nepalese Leisure Travelers’ Willingness to Travel - Dahal, Rajiv (Journal of Tourism & Adventure, 2020)
The paper aims to explore and understand COVID-19 and its effect on tourism in Nepal. More specifically, the study intends to find out Nepalese leisure travelers’ past traveling behavior and their willingness to travel once the government of Nepal relaxes the COVID-19 related lockdown and measures. The study used exploratory research design and used a survey method to find out respondents’ opinions on aspects of COVID-19 and tourism. The use of convenience sampling for collecting responses yielded 316 responses through email and social media platforms that lasted for three weeks in June - July 2020. The research revealed that most of the respondents are less affected by COVID-19 and are willing to take a holiday/vacation once there is relaxation of the COVID-19 measures. The majority of the respondents believed tourism as a significant part of the Nepalese economy, and expected tourism in Nepal would recover from the COVID situation.